Student Misconceptions in Solving AKM Numeration Problems at SMA Level Viewed From the Personality Differences of Extrovert And Introvert Students - Nisa Alawiyah Gunawan; Yandi Heryandi; Muhamad Ali Misri (Journal of Mathematics Instruction, Social Research and Opinion, 2023)
This study aims to analyze: (1) Knowing personality types, (2) Results from AKM Numeracy, and (3) Misconceptions about AKM Numeracy based on personality types based on student personality types. This type of research is descriptive qualitative research with a case study design. The data collection technique was done by giving personality questionnaires and AKM Numerical test questions. The results showed that: (1) The tendency of personality types in extroverted students was 36%, and the other 64% had introverted tendencies, (2) The results of completing the AKM Numeracy test had the highest percentage in the misconception category, namely 50.40%, 26.20 % understand the concept, and the other 23.20% do not understand the concept, (3) Misconceptions in AKM Numeracy based on student personality types, shows that the highest misconceptions are found in students with extrovert personality types, with an average percentage of 55.80%, while students with introverted personality types have a percentage of 51.25%. Factors causing these misconceptions include acquiring student answers, studying habits, and the learning media used.